Experimentação e materiais alternativos: um olhar para a formação inicial dos professores de química - Silva, Maria Verônica da (2019)
At present it is possible to perceive the need for renewal in the ways of teaching and learning that can contribute to the improvement of teaching. In the case of Chemistry teaching, experimental activities are presented as a methodology capable of promoting the relationship between theory and practice, where students can perceive several concepts that are difficult to visualize in strictly theoretical classes. In this context, the low-cost materials that are used in daily activities can be included in the lesson plans, serving to replace equipment and reagents as well as helping students visualize the application of the studied contents. Despite the various discussions about the importance of such In the initial training, few approaches to this subject are observed. In this way, this dissertation aims to investigate what is expected for the initial training courses of Chemistry teachers, regarding experimentation and alternative materials, as well as the approaches and works done on this subject by teachers and students For this purpose, this research was carried out in the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN) - Campus Apodi, through four stages, realization of a state of knowledge regarding the subject of experimentation and alternative materials, PPC of the Degree in Chemistry with the objective of verifying if there are references in the document to the subject under study, individual interviews with teachers who act in the course and interviews with focus group to a group of the 8th period of said course. As for the analysis of knowledge state data, PPC of the course and interviews was used the method of content analysis of Bardin (1977). After the research was completed it was possible to notice that with regard to the state of knowledge that there are several publications related to the theme but that they are limited to proposals more there are few publications that refer to activities that have actually been applied in schools. In the PPC, there were few references to the subject, the interviews with the teachers showed that they recognize the importance of alternative materials for the improvement of the teaching of Chemistry, however it is noted that there are few studies that are developed in the course related to the subject, finally, the students also demonstrate the subject and have already developed related activities